2023
DOI: 10.3390/ijms241210406
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Vehicle-Based Approach for Cardiac Cell Transplantation Leads to Rapid Electromechanical Graft–Host Coupling

Aleria Aitova,
Serafima Scherbina,
Andrey Berezhnoy
et al.

Abstract: Myocardial remodeling is an inevitable risk factor for cardiac arrhythmias and can potentially be corrected with cell therapy. Although the generation of cardiac cells ex vivo is possible, specific approaches to cell replacement therapy remain unclear. On the one hand, adhesive myocyte cells must be viable and conjugated with the electromechanical syncytium of the recipient tissue, which is unattainable without an external scaffold substrate. On the other hand, the outer scaffold may hinder cell delivery, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Moreover, a fragment of a single biocompatible polymer fiber of subcellular size may be used as a minimized "one-dimensional" polymer substrate itself. It was shown that fragments of PLLA or silk fibroin nanofibers with fibronectin coating may be used as effective scaffolds for solitary cardiomyocytes during cell transfer in vitro [158] and in vivo [159], supporting the organization of myofibrils and cytoskeleton of cells in suspension and restoring the cell excitability before adhesion to the recipient cell monolayer layer or tissue, respectively. Thus, such kernel substrates may be effectively used for in vitro modeling of cell transplantation processes in arrhythmia studies.…”
Section: Variety Of Substrates For Biomimetic Cardiac Tissue Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a fragment of a single biocompatible polymer fiber of subcellular size may be used as a minimized "one-dimensional" polymer substrate itself. It was shown that fragments of PLLA or silk fibroin nanofibers with fibronectin coating may be used as effective scaffolds for solitary cardiomyocytes during cell transfer in vitro [158] and in vivo [159], supporting the organization of myofibrils and cytoskeleton of cells in suspension and restoring the cell excitability before adhesion to the recipient cell monolayer layer or tissue, respectively. Thus, such kernel substrates may be effectively used for in vitro modeling of cell transplantation processes in arrhythmia studies.…”
Section: Variety Of Substrates For Biomimetic Cardiac Tissue Modelsmentioning
confidence: 99%
“…Cell transfer experiments in vivo show that the use of polymer kernel substrates leads to rapid electromechanical graft-host coupling: the synchronization of transplanted cells with isolated rat heart contractions (and consequently with each other) takes only 30 min after the first contact, while in the absence of any substrate, such a process may be chaotic, accompanied by engraftment arrhythmia, and would require several hours or even days [159].…”
Section: Variety Of Substrates For Biomimetic Cardiac Tissue Modelsmentioning
confidence: 99%